Synthesis and characterization of reduced graphene oxidation from corn cob waste - Dyah Suci Perwitasari; Adinata Shafi Wahyudi Suwarno; Muhammad Nauli Rizqi Akbar (Jurnal Pendidikan Kimia (JPKIM), 2022)
Graphene is the latest carbon-based nanomaterial with wide applications and has superiority in electrical, thermal, and high conductivity properties. This study aims to synthesize and characterize reduced graphene oxide (rGO) from corncob waste using the modified Hummer method. which was carried out by removing the NaNo3 material. This synthesis used corncob waste that was made into charcoal with a particle size of 100 mesh with an oxidation time of 5 days. Structural analysis of rGO used Fourier Transform Infa Red (FTIR) and X-ray diffraction (XRD) testing. The results of FTIR testing showed a wave peak at 1568.82 cm-1 with C=C bonds which indicated that rGO was formed. The XRD test results showed a diffractogram peak at an angle of 2θ ~ 24.6635 which is typical of rGO materials.Keywords: Corncob waste; Graphene; Graphite; Modified hummer; rGO